Investigation of Domestic Wastewater Treatment and Electricity Generation Using A Two Chambered Microbial Fuel Cell with Composite Anode Electrode - Akçay, Gizem Hazan; Ar, İrfan (My University, 2023)
Microbial fuel cell is a bioelectrochemical system that generate electricity with the oxidation of organic substrates by exoelectrogenic microorganisms. It can be said that the studies on microbial fuel cells (MFCs) are generally aimed to increase the amount of energy produced. In this study, domestic wastewater treatment was investigated by using a two-chamber microbial fuel cell. Ankara Tatlar Wastewater Treatment Plant influent water was used as substrate. In order to reduce the diffusional resistance by reducing the distance between the anode and cathode electrode, the cathode chamber was placed in the middle of the anode chamber. Anode and cathode chambers separated by Nafion 117 membrane. In addition, an anode consisting of a stainless-steel mesh and a graphite supported catalyst has been developed to increase the electricity generation potential. During the experiment, the maximum voltage and the maximum power density values were obtained as 595 mV and 205.867 mW/m2 respectively. COD value is a criteria which indicates the waste treatment ability of the systems. For this experiment COD values of the wastewaster were measured both the beginning and the end of the experiment as 451 mg/L O2 and 361 mg/L O2. These results proved that the developed electrode structure is at a comparable level with the values reported in the literature for two-chamber MFC studies.
Keywords: Electricity generation; microbial fuel cell; composite electrode; domestic wastewater treatment